Clinicopathological significance of c-MYC in esophageal squamous cell carcinoma - Yu Lian; Xiangdong Niu; Hui Cai; Xiaojun Yang; Haizhong Ma; Shixun Ma; Yupeng Zhang; Yifeng Chen (Tumor Biology)
Esophageal squamous cell carcinoma is one of the most common malignant tumors. The oncogene c-MYC is thought to be important in the initiation, promotion, and therapy resistance of cancer. In this study, we aim to investigate the clinicopathologic roles of c-MYC in esophageal squamous cell carcinoma tissue. This study is aimed at discovering and analyzing c-MYC expression in a series of human esophageal tissues. A total of 95 esophageal squamous cell carcinoma samples were analyzed by the western blotting and immunohistochemistry techniques. Then, correlation of c-MYC expression with clinicopathological features of esophageal squamous cell carcinoma patients was statistically analyzed. In most esophageal squamous cell carcinoma cases, the c-MYC expression was positive in tumor tissues. The positive rate of c-MYC expression in tumor tissues was 61.05%, obviously higher than the adjacent normal tissues (8.42%, 8/92) and atypical hyperplasia tissues (19.75%, 16/95). There was a statistical difference among adjacent normal tissues, atypical hyperplasia tissues, and tumor tissues. Overexpression of the c-MYC was detected in 61.05% (58/95) esophageal squamous cell carcinomas, which was significantly correlated with the degree of differentiation (p = 0.004). The positive rate of c-MYC expression was 40.0% in well-differentiated esophageal tissues, with a significantly statistical difference (p = 0.004). The positive rate of c-MYC was 41.5% in T1 + T2 esophageal tissues and 74.1% in T3 + T4 esophageal tissues, with a significantly statistical difference (p = 0.001). The positive rate of c-MYC was 45.0% in I + II esophageal tissues and 72.2% in III + IV esophageal tissues, with a significantly statistical difference (p = 0.011). The c-MYC expression strongly correlated with clinical staging (p = 0.011), differentiation degree (p = 0.004), lymph node metastasis (p = 0.003), and invasion depth (p = 0.001) of patients with esophageal squamous cell carcinoma. The c-MYC was differentially expressed in a series of human esophageal tissues, and the aberrant c-MYC expression could be a potential factor in carcinogenesis and progression of esophageal squamous cell carcinoma. There was a statistical signification for c-MYC in esophageal squamous cell carcinoma patients to analyze clinicopathological features. It possibly becomes a new diagnostic indicator of esophageal squamous cell carcinoma.